2003
DOI: 10.1152/japplphysiol.00399.2003
|View full text |Cite
|
Sign up to set email alerts
|

Preventing annoyance from odors in spaceflight: a method for evaluating the sensory impact of rodent housing

Abstract: For the scientific community, the ability to fly mice under weightless conditions in space offers several advantages over the use of rats. These advantages include the option of testing a range of transgenic animals, the ability to increase the number of animals that can be flown, and reduced demands on shuttle resources (food, water, animal mass) and crew time (for water refill). Mice have been flown in animal enclosure module (AEM) hardware only once [Space Shuttle Transport System (STS)-90] and were dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…This study represents the first flight of mice on the space shuttle, an important development in the use of animal models in microgravity. As such, we have demonstrated that the young mouse can be considered an applicable model for spaceflight-induced osteopenia [34]. Previous studies of pre-and post-flight finite element models of astronaut's proximal femur following 4.3-6.5 month stays on the International Space Station (ISS) have demonstrated a rapid decline in estimated strength of the proximal femur, on the order of 2.0-2.6% per month [10].…”
Section: Discussionmentioning
confidence: 85%
“…This study represents the first flight of mice on the space shuttle, an important development in the use of animal models in microgravity. As such, we have demonstrated that the young mouse can be considered an applicable model for spaceflight-induced osteopenia [34]. Previous studies of pre-and post-flight finite element models of astronaut's proximal femur following 4.3-6.5 month stays on the International Space Station (ISS) have demonstrated a rapid decline in estimated strength of the proximal femur, on the order of 2.0-2.6% per month [10].…”
Section: Discussionmentioning
confidence: 85%
“…Each participant was asked to refrain from smoking, eating or drinking for at least one hour prior to testing. Prior to the first test, all individuals were screened for normal olfactory function using the NASA Odor Screening Test, which is a 7-item olfactory evaluation method adopted from an ASTM standard method (Dalton et al 2003)…”
Section: Methodsmentioning
confidence: 99%
“…This testing was seen as especially important for the paint chemists given the nature of their occupation and their probable history of exposure to solvents, which can alter and impair olfactory sensitivity , . Three types of tests were used: detection sensitivity for phenylethyl alcohol, forced-choice discrimination of five qualitatively different odorous chemicals (phenylethyl alcohol, amyl acetate, eucalyptol, menthone, and acetic acid) and a 20 item odor identification test, consisting of numerous everyday food and household odors , .…”
Section: Methodsmentioning
confidence: 99%